Cutaneous α-synuclein is correlated with autonomic impairment in isolated rapid eye movement sleep behavior disorder. Issue 12 (9th July 2021) - Miglis, Mitchell G; Zitser, Jennifer; Schneider, Logan; During, Emmanuel; Jaradeh, Safwan; Freeman, Roy; Gibbons, Christopher H
Abstract: Study Objectives: To define the clinical implications of cutaneous phosphorylated α-synuclein (p-syn) and its association with subjective and objective measures of autonomic impairment and clinical features including antidepressant use in isolated rapid eye movement (REM) sleep behavior disorder (iRBD). Methods: Twenty-five iRBD patients had quantified neurological and cognitive examinations, olfactory testing, questionnaires, autonomic function testing, and 3 punch skin biopsies (distal thigh, proximal thigh, neck). Skin biopsies were stained for the pan-axonal marker PGP 9.5 and co-stained with p-syn, and results were compared to 28 patients with Parkinson's disease (PD) and 18 healthy controls. Equal numbers of iRBD patients on and off antidepressants were recruited. The composite autonomic severity scale (CASS) was calculated for all patients. Results: P-syn was detected in 16/25 (64%) of iRBD patients, compared to 27/28 (96%) of PD and 0/18 controls. The presence of p-syn at any biopsy site was correlated with both sympathetic (CASS adrenergic r = 0.6, p < 0.05) and total autonomic impairment (CASS total r = 0.6, p < 0.05) on autonomic reflex testing in iRBD patients. These results were independent of the density of p-syn at each site. There was no correlation between p-syn and antidepressant use. Conclusions: In patients with iRBD, the presence of cutaneous p-syn was detected in most patients and was associated with greater autonomic dysfunction on testing. Longitudinal follow-up will aid in defining the predictive role of both skin biopsy and autonomic testing in determining phenoconversion rates and future disease status.